Googling caesarean section: a survey on the quality of the information available on the Internet. (11th September 2014) - Fioretti, BTS; Reiter, M; Betrán, AP; Torloni, MR
Abstract : Objective: To examine the quality and completeness of information on caesarean section in web pages used by laypersons in Brazil, a country with very high rates of caesarean delivery. Design: Cross‐sectional study. Setting: Brazil. Sample: A total of 176 Internet websites. Methods: The term 'caesarean delivery' and 25 synonyms were entered into the most popular search engines in Brazil. The first three pages of hits were downloaded and assessed by two independent investigators using the DISCERN instrument and a content checklist. Main outcome measures: Quality and completeness of information on caesarean section. Results: A total of 3900 web pages were retrieved and 176 fulfilled the selection criteria. The overall average DISCERN score was 43.6 (±8.9 SD), of a maximum score of 75; 30% of the pages were of poor or very poor quality and 47% were of moderate quality. Most pages scored low, especially in questions related to reliability of the information. The most frequently covered topics were: indications for caesarean section (80% of websites), which did not reflect clinical practice; short‐term maternal risks (80%); and potential benefits of caesarean section (56%), including maternal and doctor convenience. Less than half of the websites mentioned perinatal risks and less than one‐third mentioned long‐term maternal risks associated with caesarean section, such as uterine rupture (17%) or placenta praevia/accreta (12%) in future pregnancies. Conclusions: The quality and completeness of web‐based resources in Portuguese about caesarean section were poor to moderate. Pending improvement of these resources, obstetricians should warn pregnant women about these facts and encourage them to discuss what they have read on the Internet about caesarean section. Tweetable abstract: The quality and completeness of information about caesareans is poor in 176 websites used by Brazilians.